2010
DOI: 10.1038/leu.2009.281
|View full text |Cite
|
Sign up to set email alerts
|

Selective elimination of a chemoresistant side population of B-CLL cells by cytotoxic T lymphocytes in subjects receiving an autologous hCD40L/IL-2 tumor vaccine

Abstract: Side-population (SP) analysis identifies precursor cells in normal and malignant tissues. Cells with this phenotype have increased resistance to many cytotoxic agents, and in malignant disease may represent a primary drug resistant population. To discover whether drug resistant malignant SP cells are nonetheless sensitive to immune-mediated killing, we first established the presence of a malignant CD5+CD19+ SP subset in the blood of 18/21 subjects with B-CLL. We examined the fate of these cells in 6 of these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
(77 reference statements)
3
15
0
Order By: Relevance
“…Confirming a recent publication, 22 here we reported the existence of few natural SP cells in virtually all B-CLL patients, which harbors phenotypic and cytogenetic hallmarks of the disease. Although they are chemoresistant, B-CLL SP cells are present in patients before any treatments.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Confirming a recent publication, 22 here we reported the existence of few natural SP cells in virtually all B-CLL patients, which harbors phenotypic and cytogenetic hallmarks of the disease. Although they are chemoresistant, B-CLL SP cells are present in patients before any treatments.…”
Section: Discussionsupporting
confidence: 69%
“…20,21 In this study, we tracked chemoresistant subsets of B-CLL cells by the SP technique to clarify the dynamics of chemoresistance in this disease. Our study confirms the existence of Fludarabine-resistant leukemic SP cells in B-CLL, as established recently by Foster et al 22 In addition to uncovering both innate and acquired cell compartments with SP phenotype, this report addresses the question of polyresistance displayed by the B-CLL SP cells and demonstrates the prevalence of this population in post-therapeutic B-CLL samples. Finally, this study attempted to characterize SP cell dynamics underlying successive B-CLL relapses with progressive chemoresistance.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We have also shown that treatment of tumor cells with demethylating agents led to upregulation of PRAME expression (C. C. Chang, MD, PhD, unpublished data, November 2011). As mentioned above, studies by Shafer et al 34 and Foster et al 32,33 demonstrated selective susceptibility of SP cells in chronic lymphocytic leukemia and Hodgkin lymphoma to cytotoxic T cells.…”
Section: Cancer/testis Antigens As Csc Immunotherapy Targetsmentioning
confidence: 94%
“…Foster et al 32,33 generated cytotoxic lymphocytes directed against a stem cell-like SP of cells in chronic lymphocytic leukemia. The same group similarly demonstrated the potential cytotoxicity of cytotoxic lymphocytes against SP cells in Hodgkin lymphoma.…”
Section: Csc Drug Resistancementioning
confidence: 99%